Fenomenologi Pemahaman dan Makna KIP oleh PPID Dinas Pariwisata Provinsi Sumatera Barat - Rahmadhona Fitri Helmi; Karjuni Dt Maani; Aldri Frinaldi (Journal of Education on Social Science (JESS), 2020)
The ability of the government to provide the availability of information with a variety of infrastructure and adequate content, accompanied by an attitude of openness and adequate mechanisms and procedures will facilitate the public to contribute or participate positively. The provision of information in the government is carried out by Public Information Management Officers (PPID) in each Public Agency. This research was conducted to find out how the understanding of PPID in the West Sumatra Province Tourism Office towards public information disclosure, knowing the meaning of information applicants and knowing the meaning of public information openness by the PPID in the West Sumatra Province Tourism Office. The method used in this study is a qualitative method with a phenomenological approach. The results showed that the understanding of PPID in the West Sumatra Province Tourism Office towards public information disclosure is quite good. The PPID is able to take responsibility for the mandate of Law Number 14 Year 2008 on Public Disclosure of information, which is responsible for storing, documenting and providing public information by supplying public information data available at the West Sumatra Province Tourism Office to the PPID in West Sumatra Province Government. The meaning of information applicants for PPID in the Tourism Office of West Sumatra Province is as a party that must be served and has the right to obtain public information because they are guaranteed by the Public Disclosure of information Law. While the meaning of public information disclosure for PPID in the West Sumatra Province Tourism Office is the guarantee for the public to get information from public agencies. Keywords: Public Information Disclosure Act, Information Public, Officials Manager of Information and Documentation